Perancangan Interior Sevier Industry Kerajinan Barang Jadi Kulit di Surabaya - Syeli Deamartha (Intra, 2017)
Starting from the idea of building a bussiness based on creativity using surabaya’s local potention. Handmade leathergoods is now being a concept for the new economic growth in this modern era that creating awareness to support this kind of creativity. Retail shop is needed to gain the sales and same thing go for a workshop to facilitate training for the leathercrafter. This design focused on the standartisation of the interior that being a part from the branding of the product itself like the furniture, lightning, and the room settings will give a direct impact in the process of creating leathergoods. Sevier industry is a facility for people to introduce leathergoods, give inspiration for them, and being a source of leathergoods knowladge that shows the area of education applicated to gallery and workshop area. Fresh monochrome concept will used in the commercial and the longe of the leathergoods store that inspired by industrial style design to applicated in each of every corner of the area.